Spatial Distribution and Evolution of Ancient Settlements From the Neolithic to the Bronze Age in Dalian Area, China - Liu, Liang; Liu, Fangfang; Zhang, Wei; Xu, Zhaofeng (Frontiers in Earth Science, 2022)
ArcGIS software was used to analyze the spatial distribution of Mid Holocene (i.e., 6.7-3.1 ka BP) human settlements and sites in the Dalian area. Their evolution was studied in depth alongside the Mid Holocene environmental background known to have existed. The results showed that: ① The number of ancient settlements in the Dalian area increased during this period. Most sites during the three periods studied were to be found 0 to 50 m above sea level (asl), with a significant increase in the number of sites located > 50 m asl during the Bronze Age. In terms of gradient of slope, all settlements were concentrated on coastal plains or in low-altitude, hilly areas on relatively gentle slopes ranging between 0 and 6 °. Settlements from each period faced in all directions, and were mainly located in river valleys or low-altitude mountain valleys with low terrains.② The proximity of ancient settlements to river courses during the Mid Holocene evolved, with Mid and Late Neolithic settlements usually distributed in the range beyond 3 km of the river buffer zone; the distribution of Bronze Age sites was relatively uniform, reflecting an increasing demand for water resources; the density of settlements was clustered between the Mid Neolithic and the Bronze Age, Neolithic sites being both the smallest in number and the most concentrated. ③ The spatiotemporal distribution and evolution of settlements in the Dalian area were influenced by the contemporary climate: the Mid Neolithic climate was warm and humid, and settlements were distributed principally on the various islands near present-day Dalian, and especially Guanglu Island; the Late Neolithic climate became increasingly drier and cooler, stimulating cultural advances and a slight increase in the number of ancient settlements, which gradually developed in the areas in and around present-day Dalian; during the cold and dry Bronze Age, the number of settlements across the Dalian region reached their peak, and it is widely distributed in various areas of Dalian. To a certain extent, this reflected a continuous improvement in the ability of the human population to adapt to the natural environment.